p53 gene targeting by homologous recombination in fish ES cells. - Yan Yan; Ni Hong; Tiansheng Chen; Mingyou Li; Tiansu Wang; Guijun Guan; Yongkang Qiao; Songlin Chen; Manfred Schartl; Chang-Ming Li; Yunhan Hong (PLoS ONE, 2013)
Background Gene targeting (GT) provides a powerful tool for the generation of precise genetic alterations in embryonic stem (ES) cells to elucidate gene function and create animal models for human diseases. This technology has, however, been limited to mouse and rat. We have previously established ES cell lines and procedures for gene transfer and selection for homologous recombination (HR) events in the fish medaka (Oryzias latipes). Methodology and principal findings Here we report HR-mediated GT in this organism. We designed a GT vector to disrupt the tumor suppressor gene p53 (also known as tp53). We show that all the three medaka ES cell lines, MES1∼MES3, are highly proficient for HR, as they produced detectable HR without drug selection. Furthermore, the positive-negative selection (PNS) procedure enhanced HR by ∼12 folds. Out of 39 PNS-resistant colonies analyzed, 19 (48.7%) were positive for GT by PCR genotyping. When 11 of the PCR-positive colonies were further analyzed, 6 (54.5%) were found to be bona fide homologous recombinants by Southern blot analysis, sequencing and fluorescent in situ hybridization. This produces a high efficiency of up to 26.6% for p53 GT under PNS conditions. We show that p53 disruption and long-term propagation under drug selection conditions do not compromise the pluripotency, as p53-targeted ES cells retained stable growth, undifferentiated phenotype, pluripotency gene expression profile and differentiation potential in vitro and in vivo. Conclusions Our results demonstrate that medaka ES cells are proficient for HR-mediated GT, offering a first model organism of lower vertebrates towards the development of full ES cell-based GT technology.